ADSORPSI ZAT WARNA METILEN BIRU DENGAN KARBON AKTIF DARI KULIT DURIAN MENGGUNAKAN KOH DAN NaOH SEBAGAI AKTIVATOR - Farida Hanum, Rikardo Jgst Gultom, Maradona Simanjuntak (Universitas Sumatera Utara, 2017)
Durian is a kind of tropical fruits which can grow well in Indonesia. Durian is containing 60-75% shell. Durian shell could be a potential alternative to activated carbon because it contains 57.42% carbon. The aim of this research is to know the effect of contact time and stirring speed to activated carbon adsorption capacity from durian shell with KOH and NaOH as activators. FTIR (Fourier Transform Infra Red) analysis showed the activation process effects on absorption intensity wavelength region and resulted in formation of C = C aromatic tape, so that the nature of the charcoal becomes more polar compared with the initial condition. Analysis using spectrophotometer UV-Vis to determine absorbance and final concentration of each variation of contact time and stirring speed. The results showed that the maximum adsorption capacity obtained by activation of KOH and NaOH on stirring speed of 150 rpm and a contact time of 90 minutes is equal to 3.92 mg / g and 3.8 mg / g respectively. The maximum surface area obtained by activation of KOH and NaOH during the stirring speed 130 rpm and a contact time of 120 minutes is equal to 1785.263 m2 / g and 1730.332 m2 / g respectively. The maximum surface area obtained from this research has met the standards of commercial activated carbon surface area was between 800-1800 m2/ g. Modeling pseudo second order presents a more representative adsorption data, a second order equation is based on the assumption that adsorption step is chemosorption.